2016
DOI: 10.1039/c6ew00150e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chemical structure on the sonochemical degradation of perfluoroalkyl and polyfluoroalkyl substances (PFASs)

Abstract: The study provides insights into the effect of carbon chain length, functional group substitutions and chemical structure on sonochemical degradation of perfluoroalkyl and polyfluoroalkyl substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 48 publications
(82 reference statements)
3
36
1
Order By: Relevance
“…Sonolytic degradation of PFOA ( Figure 1a (pseudo first order), are lower than previously reported values in the literature [10][11][12]33]. This is due to lower ultrasound power density (77 W L -1 ) and power intensity (0.69 W cm -2 ) in this study compared to 250 W L -1 and 6.4 W cm -2 used by [11] for a similar initial concentration (20 μM) of PFOA and PFOS.…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Sonolytic degradation of PFOA ( Figure 1a (pseudo first order), are lower than previously reported values in the literature [10][11][12]33]. This is due to lower ultrasound power density (77 W L -1 ) and power intensity (0.69 W cm -2 ) in this study compared to 250 W L -1 and 6.4 W cm -2 used by [11] for a similar initial concentration (20 μM) of PFOA and PFOS.…”
Section: Resultscontrasting
confidence: 63%
“…Campbell and Hoffman (2015) observed insignificant degradation of PFAS at an ultrasonic frequency of 20 kHz using probe sonication [9]. Many studies reported highfrequency ultrasound (> 202 kHz), which uses a vibrating flat plate transducer, as a promising technology to mineralize PFOA and PFOS [10][11][12]. However, the sonochemical process optimization would benefit from a deeper understanding of the dynamics of PFAS adsorption at the collapsible cavity-water interface.…”
Section: Introductionmentioning
confidence: 99%
“…Sonolysis appears to destroy a wide range of PFAS compounds (long chain and short chain), with consistent observations of pseudo-first order rate kinetics and faster kinetics for larger PFASs with more fluorination (perfluorinated > polyfluorinated; Fernandez et al, 2016;Rayne & Forest, 2009;Rodriguez-Freire et al, 2016;Rodriguez-Freire et al, 2015). One limitation of the available sonolysis data for PFASs is that the focus is on viability and, therefore, high concentrations of PFAS are used (>10,000 ng/L).…”
Section: Sonolysismentioning
confidence: 57%
“…When the microbubbles are collapsed during compression cycles, significant energy is released in the form of heat, and literature observations suggest achievable temperatures of up to 5,000 degrees Kelvin within the bubbles (Campbell, Vecitis, Mader, & Hoffmann, ). For scale‐up, there are many optimization factors that can be explored (sound field distribution, bubbling gas in‐line, pH changes, and changing the external temperature and pressure) as well as the generation of the hydroxyl radical, which may have varying degrees of success for different PFAS (Cheng, Vecitis, Park, Mader, & Hoffmann, ; Drees, ; Fernandez, Rodriguez‐Freire, Keswani, & Sierra‐Alvarez, ; Hao, Guo, Wang, Leng, & Li, ; Mason, ; Moriwaki et al., ; Rayne & Forest, ; Rodriguez‐Freire, Balachandran, Sierra‐Alvarez, & Keswani, ; Vecitis, Park, Cheng, Mader, & Hoffmann, ; Vecitis et al., ).…”
Section: Electrochemical Oxidationmentioning
confidence: 99%
See 1 more Smart Citation